2018
DOI: 10.1007/s00421-018-3973-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-week betalain-rich beetroot concentrate supplementation on cycling performance and select physiological parameters

Abstract: We report that 7 days of BLN supplementation modestly improves 30-min TT power output, exercise efficiency as well as post-exercise blood flow without increasing plasma NOx levels or altering blood markers of inflammation, oxidative stress, and/or hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Nutritional supplements or dietary ingredients which promote vasodilation may be beneficial for increasing blood flow to working muscle during and following exercise (reviewed in [1,2]). Common dietary supplements that have been examined in this regard have included high nitratecontaining beet root juice [3][4][5][6][7][8], L-arginine [9], L-citrulline [10][11][12], betalains [13], and various plant extracts (e.g., red spinach) [14]. Most of these supplements have been posited to act through increasing endothelium-dependent nitric oxide (NOx) production which, in turn, stimulates smaller artery and arteriole vasodilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional supplements or dietary ingredients which promote vasodilation may be beneficial for increasing blood flow to working muscle during and following exercise (reviewed in [1,2]). Common dietary supplements that have been examined in this regard have included high nitratecontaining beet root juice [3][4][5][6][7][8], L-arginine [9], L-citrulline [10][11][12], betalains [13], and various plant extracts (e.g., red spinach) [14]. Most of these supplements have been posited to act through increasing endothelium-dependent nitric oxide (NOx) production which, in turn, stimulates smaller artery and arteriole vasodilation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these supplements have been posited to act through increasing endothelium-dependent nitric oxide (NOx) production which, in turn, stimulates smaller artery and arteriole vasodilation. However, some supplements (e.g., betalains) appear to enhance blood flow through NOx-independent mechanisms [13]. Additionally, while numerous independent laboratories have reported beet root juice increases humoral NOx levels and vasodilation, other supplements (e.g., L-arginine and L-citrulline) have not shown consistent results (reviewed in [2]).…”
Section: Introductionmentioning
confidence: 99%
“…Two of the aforementioned studies [52,53] and several others since (see [41] for review) have used a nitrate-depleted, but otherwise nutritionally identical, beetroot juice drink as a placebo, suggesting that nitrate was the bioactive constituent largely responsible for these beneficial physiological effects. However, recent research has shown that betalains, the group of pigments found in beetroot that provide its purple hue, can also increase exercise tolerance in healthy young subjects, indicating that nitrate might not be the only ingredient in beetroot with ergogenic effects [57,58]. Although the mechanisms underpinning such improvements are unclear, betalains are known to have potent antioxidant effects [33].…”
Section: Exercise Tolerance In Athletesmentioning
confidence: 99%
“…Such effects are believed to attenuate exercise-induced oxidative stress, which has been associated with fatigue during high-intensity exercise [59]. Thus, the betalains present in beetroot could enhance exercise performance independent of any physiological effects of nitrate and its subsequent conversion to NO [58][59][60]. Finally, a study by Porcelli et al found that a short-term high-nitrate diet (~8.2 mmol/day of nitrate) significantly improved exercise performance compared with performance associated with the control diet (~2.9 mmol/day of nitrate) [61], suggesting that future studies are needed to examine the effects of beetroot juice on exercise performance compared with the effects of a high-nitrate diet from other vegetable sources.…”
Section: Exercise Tolerance In Athletesmentioning
confidence: 99%
“…Moreover, betanin has also been demonstrated to possess antiapoptotic properties [46]. Last but not least, betalain-rich concentrates have been shown to improve running, cycling and exercise performances [49,50]. However, it should be noted that betanin beneficial effects are challenged by its relatively low bioavailability [40,[51][52][53].…”
Section: Introductionmentioning
confidence: 99%